Public perception of solid waste collection service towards effective waste management: case study at Taman Samarindah, Kota Samarahan / Galana Intan Ngelai and Shaznaac Chervilian Mijar - Ngelai, Galana Intan; Mijar, Shaznaac Chervilian (2024)
The elements and factors that contribute to the public perception of effective waste management are examined in this study. We have chosen this topic to be studied because this study is easier to understand and can be easier for other researchers and the public. The study found that waste management, solid waste collection services, and level of awareness are the factors that contributed to the public perception. We found that improving these elements may improve UiTM Kota Samarahan students' knowledge-sharing culture. This study expands our understanding of academic information sharing and has implications for educators and policymakers seeking to foster collaborative learning cultures. This research focuses on the relationship between the level of awareness and public perception. The outcome of this relationship is the solution for the solid collection service improvement. Our selected respondents are the residents of Taman Samarindah, Kota Samarahan. The questionnaire was distributed to the 378 respondents in Taman Samarindah, Kota Samarahan.